2020
DOI: 10.2131/jts.45.411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intragastric administration of La<sub>2</sub>O<sub>3</sub> nanoparticles on mouse testes

Abstract: Lanthanum oxide (La 2 O 3) nanoparticles (NPs) have been widely used in photoelectric and catalytic applications. However, their exposure and reproductive toxicity is unknown. In this study, the effect of the intragastric administration of two different-sized La 2 O 3 particles in the testes of mice for 60 days was investigated. Although the body weight of mice treated or not treated with La 2 O 3 NPs was not different and La 2 O 3 NPs were distributed in the organs including the testis, liver, kidney, spleen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Numerous studies have demonstrated that NPs such as graphene, 32 SiO 2 -NPs, 33 Ag-NPs, 23 ZnO-NPs, 24 and La 2 O 3 -NPs 34 can significantly decrease the occludin protein level and increase the paracellular permeability in various biological barriers. In many of these studies, NPs were exposed at high doses or for extended periods, resulting in severe global cytotoxicity.…”
Section: Nanoparticles Interact With the "Gatekeepers" To Regulate Pa...mentioning
confidence: 99%
“…Numerous studies have demonstrated that NPs such as graphene, 32 SiO 2 -NPs, 33 Ag-NPs, 23 ZnO-NPs, 24 and La 2 O 3 -NPs 34 can significantly decrease the occludin protein level and increase the paracellular permeability in various biological barriers. In many of these studies, NPs were exposed at high doses or for extended periods, resulting in severe global cytotoxicity.…”
Section: Nanoparticles Interact With the "Gatekeepers" To Regulate Pa...mentioning
confidence: 99%
“…It has been shown that cerium oxide nanoparticles (CeO 2 NPs) increase the amount of Ce in mouse testes, causing pathological damage to testicular tissue and reduced sperm viability and survival [ 5 ]. Lanthanum oxide (La 2 O 3 ) nanoparticles (NPs) are distributed in mouse testes and cross the blood–testis barrier, causing apoptosis of mouse spermatogenic cells [ 6 , 16 ]. Nd 2 O 3 enters the body mainly in the form of dust or aerosols through the respiratory tract and then travels through the bloodstream to cause damage to various organs, of which the male reproductive organs are more sensitive than other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that rare earth cerium oxide particles (CeO 2 NPs) can increase the content of Ce element in mouse testis, cause pathological damage to testicular tissue, and reduce sperm viability and survival rate [ 5 ]. Other studies also show that rare earth lanthanum oxide particles (La 2 O 3 NPs) penetrate the blood–testis barrier of mice and accumulate in testicular tissue to cause apoptosis of spermatogenic cells [ 6 ]. However, the underlying mechanisms of reproductive damage have not been explicitly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The increased malondialdehyde and 8-OHdG activity and decreased SOD activity indicate that oxidative DNA damage may occur early after La 2 O 3 NPs exposure. 15 Yuan et al 15 has reported oxidative stress-mediated inflammation in toxicity of La NPs on the testicular cells. Angiotensin II has a detrimental role in the pathogenesis of chronic liver disease through possessing pro-oxidant, fibro genic, and pro-inflammatory impact in the liver.…”
Section: Discussionmentioning
confidence: 99%